2014
DOI: 10.1128/aac.02545-14
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of bla CTX-M-1 /IncI1/ST3 and bla CMY-2 /IncI1/ST2 Plasmids in Healthy Urban Dogs in France

Abstract: bIn the community, close contacts between humans and dogs may promote the transfer of extended-spectrum beta-lactamase/ plasmidic AmpC cephalosporinase (ESBL/pAmpC) genes. Large-scale prevalence studies on ESBL/pAmpC carriage in dogs are rare, and data on ESBL/pAmpC plasmids are even more limited. Here, a considerable rate of 18.5% ESBL/pAmpC carriers was found among 368 unrelated healthy dogs in Paris, France. This prevalence is much higher than the one found in healthy humans in the same city (6%) but close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
36
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 35 publications
8
36
4
Order By: Relevance
“…Consistent with other studies [8,11,30], isolates (n = 10) displaying an ESBL phenotype could also be collected from healthy animals. Although the inclusion criteria comprised the absence of antimicrobial administrations in the preceding four months, the lack of information about each animal's medical history, namely antibiotic treatments prior to that period, precludes the study of how these variables influenced the resistance selection.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with other studies [8,11,30], isolates (n = 10) displaying an ESBL phenotype could also be collected from healthy animals. Although the inclusion criteria comprised the absence of antimicrobial administrations in the preceding four months, the lack of information about each animal's medical history, namely antibiotic treatments prior to that period, precludes the study of how these variables influenced the resistance selection.…”
Section: Discussionsupporting
confidence: 63%
“…Most of the current scientific literature reporting the presence of ESBL-producing E. coli in animals has focused on production animals (cattle, swine, rabbits) and wild animals (gulls and birds of prey) [6,7]. However, recent corresponding studies focusing on companion animals have started to be performed [8][9][10][11][12][13]. Since dogs and cats are kept in close contact with their owners, silent within-household transmission of resistant bacteria and resistance genes may occur in either direction by direct contact or, indirectly, through household surfaces and objects contaminated by feces, oral secretions or urine [3,14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Thus, these isolates are not easily available in Denmark. Continuous monitoring is warranted in consideration of the occurrence of these bacteria as contaminants in poultry products and as commensals in dogs (11,33). In this respect, our study provides useful baseline data that will enable future studies to assess whether the exposure of humans to bla CMY-2 of poultry origin will result in an increase in the frequency of this ␤-lactam resistance determinant in human clinical isolates.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, CMY-2-encoding plasmids identified in Danish dogs and Danish poultry showed limited diversity within the respective host species. The majority (n ϭ 12; 71%) of canine isolates harbored bla CMY-2 on IncI1-I␥/ST2 plasmids, also a predominant plasmid type in E. coli isolates from healthy dogs in France (33). This finding differs from reports of bla CMY-2 on a broad variety of plasmid types in canine isolates from the United States, Italy, and South Korea (16,28,34), highlighting geographical differences in regard to the plasmid vectors carrying bla CMY-2 in E. coli of canine origin.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Netherlands, there was an increase from 0.9% in 2004 to 7% in data published in 2016. [5][6][7][8][9][10][11][12][13] Vanessa Schmidt concluded that MDR strains were common in the population studied. It is increasingly important to obtain bacterial cultures before treatment.…”
mentioning
confidence: 99%